2020
DOI: 10.1016/j.ssmph.2020.100663
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic differences in the associations between social integration, C-reactive protein and depressive symptoms

Abstract: This study evaluates whether the associations between social integration, inflammation, and depressive symptoms vary by race/ethnicity in the United States. Our study includes 5,634 respondents age 40 and older from the National Health and Nutrition Examination Survey for 2005-2008. We fit multivariate logistic regression models with interactions between C-reactive protein (CRP) and race/ethnicity as well as social integration and race/ethnicity to test our hypotheses. We find that social integration and CRP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 61 publications
2
10
2
Order By: Relevance
“…Overall, the present systematic review reported that most studies here retrieved, found a positive association between elevated CRP levels and depression [29,51,52,54,55,61,63,64,66,67,[69][70][71][72][73]80,81,83,[90][91][92][93][94]100]. Conversely, other studies did not confirm this association [49,50,62,68,74,76,86,88,89].…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Overall, the present systematic review reported that most studies here retrieved, found a positive association between elevated CRP levels and depression [29,51,52,54,55,61,63,64,66,67,[69][70][71][72][73]80,81,83,[90][91][92][93][94]100]. Conversely, other studies did not confirm this association [49,50,62,68,74,76,86,88,89].…”
Section: Discussioncontrasting
confidence: 54%
“…A cross-sectional study evaluated the association between social integration, race/ethnicity, inflammation, and depressive symptoms in US participants through the NHANES survey [51]. Participants were administered PHQ-8 and measured hs-CRP levels.…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
See 3 more Smart Citations